The goldilocks effect: the rhythms and pace of hospital life - Jeffrey Braithwaite; Louise A. Ellis; Kate Churruca; Janet C. Long (BMC, 2018)
Abstract Background While we have made gains in understanding cultures in hospitals and their effects on outcomes of care, little work has investigated how the pace of work in hospitals is associated with staff satisfaction and patient outcomes. In an era of efficiency, as speed accelerates, this requires examination. Discussion Older studies of pace in cities found that faster lifestyles were linked to increased coronary heart disease and smoking rates, yet better subjective well-being. In this debate we propose the Goldilocks hypothesis: acute care workplaces operating at slow speeds are associated with factors such as increased wait lists, poor performance and costly care; those that are too fast risk staff exhaustion, burnout, missed care and patient dissatisfaction. We hypothesise that hospitals are best positioned by being in the Goldilocks zone, the sweet spot of optimal pace. Conclusion Testing this hypothesis requires a careful study of hospitals, comparing their pace in wards and departments with measures of performance and patient outcomes.